112̅1-101̅2 double twinning in a Zircaloy-4 alloy during rolling at ambient temperature. (September 2016) - Zhang, M.; Luan, B.F.; Song, Z.L.; Xin, R.L.; Murty, K.L.; Liu, Q.
Abstract: In this paper, we report the formation of an atypical double twinning sequence in Zircaloy-4 during rolling at room temperature. The grain orientation analysis based on electron backscattering diffraction (EBSD) data reveals that this double twinning mode is of the 11 2 ̅ 1 - 10 1 ̅ 2 type, namely, the secondary 10 1 ̅ 2 twin generated within the primary 11 2 ̅ 1 twin. Based on the combinative analysis of Schmid factor and local strain accommodation, the formation and variant selection mechanism of this double twinning are discussed. Graphical abstract: (a) Inverse pole figure (IPF) map in the RD-ND plane of following 10% reduction. Grain boundaries in (a) are colored in black (> 15°) and grey (> 2°) lines. Two black circled areas in (a) extracted for a detailed analysis in magnified IPF maps are presented in (b) and (d). Boundaries in (b) and (d) are represented as follows: white lines indicate boundaries with misorientation of 85° ± 5°/ < 11 2 ̅ 0 >, blue lines indicate boundaries with misorientation of 34° ± 5°/ < 10 1 ̅ 0 > and others are the same as those in (a). The hcp unit cells are also shown. (c) misorientation angle distribution histogram and rotation axes corresponding to (a). The angle/axis relationships related to the peaks at 35° and 85° correspond to the two tensile twinning modes in Zr, namely, the 11 2 ̅ 1 tensile twin ( 34.84°/ < 10 1 ̅ 0 > ) and the 10 1 ̅ 2 tensile twin ( 85.22°/ < 11 2 ̅ 0 > ). The misorientation axis related to the peak at 60° has high Miller indices and does not belong to any established twinning modes in Zr and is produced by twinning interaction.